Effect of Y2O3 on the physical properties and biocompatibility of β–SiAlON ceramics. Issue 15 (15th October 2020) - Li, Miao; Zhang, Liguo; Zhang, Can; Xu, Enxia; Liu, Xinhong; Zhao, Fei; Sun, Xu; Chen, Huiping; Gao, Jinxing
Abstract: To investigate the effects of Y2 O3 on the physical properties and biocompatibility of β–SiAlON ceramics, β–SiAlON ceramics were prepared with Al, Si, and α–Al2 O3 powders using a direct nitriding technique. As a sintering additive, Y2 O3 helps lower the sintering temperature and forms β–SiAlON ceramics. In this study, the physical and biological properties of the prepared ceramics were investigated to evaluate their use as bone-repairing material. Experiments revealed that the main crystal composition of the sample was Si4 Al2 O2 N6, containing small amount of additional phases Y3 Al5 O12 with increasing content of Y2 O3 . The porosity and compressive strength initially decrease and then increase to their initial values, whereas the bulk density exhibits the opposite trend with an increased proportion of Y2 O3 . The proliferation of osteoblastic and angiogenic cells demonstrates that β–SiAlON and Y3 Al5 O12 have good biocompatibility; however, the sample porosity has a slight effect on the cell proliferation rate. This implies that in human tissues, bone-repairing speed can be adjusted by modifying the sample porosity or material surface roughness. Therefore, Y2 O3 can be added to β–SiAlON ceramics to regulate their microstructure, physical properties, and biological properties for tissue engineering applications.